2018
DOI: 10.1111/cen.13745
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of 68Ga‐DOTATATE PET/CT in limited disease neuroendocrine tumours and/or elevated serum neuroendocrine biomarkers

Abstract: Our study shows that Ga-DOTATATE PET/CT detected similar number of sites than combination of SRS, liver MRI and thoraco-abdominopelvic CT on region-based analysis. Ga-DOTATATE PET/CT missed half of primary lung carcinoids with ectopic Cushing's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…A recent report, having included six new EAS cases, suggested that the sensitivity of 68 Ga -SSTR PET/CT for identifying ectopic ACTHsecreting lesions (including multiple metastases) was lower than previously reported, with a sensitivity of 64% as compared to 69% for CT (183). Our literature search, on the performance of 68 Ga -SSTR-PET/CT, identified 51 patients with possible occult and covert EAS at initial morphological imaging, assuming that the diagnosis of occult/covert EAS was based on variable imaging procedures across the studies (149,183,187,188,189,190): 68 Ga -SSTR PET/CT led to the discovery of the source of EAS in 29 out of 51 patients, indicating a sensitivity of only 57%. Despite its limitations, we consider that 68 Ga -SSTR PET/CT may be a useful complementary tool in the difficult context of occult EAS, but evaluation of its performance deserves additional studies, including a significantly larger number of unselected EAS patients.…”
Section: Pet/ct Using Gallium-68 Labeled Somatostatin Receptor Ligandsmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent report, having included six new EAS cases, suggested that the sensitivity of 68 Ga -SSTR PET/CT for identifying ectopic ACTHsecreting lesions (including multiple metastases) was lower than previously reported, with a sensitivity of 64% as compared to 69% for CT (183). Our literature search, on the performance of 68 Ga -SSTR-PET/CT, identified 51 patients with possible occult and covert EAS at initial morphological imaging, assuming that the diagnosis of occult/covert EAS was based on variable imaging procedures across the studies (149,183,187,188,189,190): 68 Ga -SSTR PET/CT led to the discovery of the source of EAS in 29 out of 51 patients, indicating a sensitivity of only 57%. Despite its limitations, we consider that 68 Ga -SSTR PET/CT may be a useful complementary tool in the difficult context of occult EAS, but evaluation of its performance deserves additional studies, including a significantly larger number of unselected EAS patients.…”
Section: Pet/ct Using Gallium-68 Labeled Somatostatin Receptor Ligandsmentioning
confidence: 94%
“…In addition, published data indicates that 68 Ga-SSTR PET/CT offers better spatial resolution and anatomical detail than octreoscan and could therefore help to detect smaller tumors. In the general context of NETs, several studies suggest that 68 Ga -SSTR PET/CT is superior to octreoscan in detecting small NETs (188,189) and staging metastatic NETs (170). In the specific context of EAS, to our knowledge only one small head-to-head study (involving only five patients with EAS) directly compared the diagnostic performances of octreoscan and 68 Ga-SSTR PET/CT (188) (Fig.…”
Section: Pet/ct Using Gallium-68 Labeled Somatostatin Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine carcinomas result from cells throughout the diffuse endocrine system ( The National Comprehensive Cancer Network [NCCN], 2018a ). Most common of these are well differentiated or carcinoid tumors, which are gastroenterohepatic and pulmonary in origin and exhibit a variety of symptoms ( Gabriel et al, 2018 ). Patients may present with symptoms associated with hormonal hypersecretion (“functional” tumors) or those that are asymptomatic are considered to have “non-functional” disease ( The National Comprehensive Cancer Network [NCCN], 2018a ).…”
Section: Neuroendocrine and Adrenal Carcinomasmentioning
confidence: 99%
“…Patients may present with symptoms associated with hormonal hypersecretion (“functional” tumors) or those that are asymptomatic are considered to have “non-functional” disease ( The National Comprehensive Cancer Network [NCCN], 2018a ). Furthermore, due to the sporadic and gradual nature of tumor growth, as well as their small size, the lesions can be difficult to detect ( Gabriel et al, 2018 ).…”
Section: Neuroendocrine and Adrenal Carcinomasmentioning
confidence: 99%